ORGANIZATIONAL MODELS AS CONFIGURATIONS OF STRUCTURE, CULTURE, LEADERSHIP, CONTROL, AND CHANGE STRATEGY - Janićijević, Nebojša (Economic Annals, 2017)
Starting from the axioms of consistency, stability, contingency, and configuration, research on organizational structure, culture, control, leadership, and change management strategy has shown that their typical configurations, or models, can be differentiated according to the same two criteria: distribution of power and dominant organizational dimension. On the one hand there are models of structure, culture, control, leadership, and change management strategy that are based on an unequal, or authoritarian, distribution of power within organizations, while on the other hand there are models that are based on democratic, or equal, distribution of power. Also, on the one hand there are models of structure, culture, control, leadership, and change strategy that are based on work structure and tasks, while on the other hand there are models of these organizational components that are based on social structure, people, and their relationships. Harmonization of typical configurations of organizational structure, culture, control, leadership, and change strategy occurs due to the harmonization of the differentiation criteria. Based on this harmonization, four organizational models have been identified as typical configurations of structure, culture, control, leadership, and change strategy: the autocratic, bureaucratic, innovative, and task models. Each of these models is effective in a different environmental contingency.